Juridical Analysis of the Application of the Principle of Contractual Balance in the Law of Agreements - Irfan Ardiansyah (Faculty of Law, Universitas Pekalongan, 2021)
In the law of agreements, standard contracts have long been used in various contracts. The use of standard agreements is closely related to economic advancements that demand efficiency in cost, time, and energy expenditure. Standard agreements do not reflect the principle of balance between the parties in the agreement. The imbalance in positions in standard agreements is caused by the parties having unequal bargaining positions, resulting in